Collectie Rolf E. Stenersen. - Stenersen, Rolf (Amsterdam : Stedelijk Museum Amsterdam, 1962)
Aulie, Reidar ; Clüver, Bernt ; Corneille ; Dufy, Raoul ; Ekeland, Arne ; Enger, Erling ; Hill, Carl Fredrik ; Hoff, Tor ; Hornung, Preben ; Jakobsen, Jakob ; Johannessen, Erik Harry ; Josephson, Ernst ; Kandinsky, Wassily ; Karseboom, L. ; Karsten, Ludvig ; Klee, Paul ; Krohg, Per ; Modigliani, Amedeo ; Munch, Edvard ; Nesch, Rolf ; Picasso, Pablo ; Rom, Per ; Schiele, Egon ; Schjerfbeck, Helene ; Stromme, Olav ; Tamayo, Rufino ; Thieler, Fred ; Thygesen, Rudolph ; Villon, Jacques ; Weidemann, Jakob
biog. per kunstenaar
Collectie Rolf E. Stenersen, Stedelijk Museum Amsterdam, 29.05.1962 - 02.07.1962
Nederlands
boek